Planejamento da xploraçeão em florestas nativas manejadas da Amazônia por meio de pesquisa operacional. - Silva, Evandro Ferreira da (2019)
One of the lapses in Sustainable Forest Management (MFS) techniques is linked to the development of new technologies, which aim to minimize environmental impacts and the costs of forest exploitation, which indicates the need to improve traditional forest planning. In this context, the research proposes an alternative forest planning with the objective of optimizing the planning of the allocation of wood storage yards, thus reducing the costs of exploration, in order to improve the forest planning traditionally used in the exploitation of native forests in the Amazon. The second chapter aims to evaluate the efficiency and eventual gains of the execution of an optimized planning for the allocation of wood storage yards, compared to the execution of a traditional planning often used by forest companies in the Amazon region. The study area of the first chapter was the Saracá-Taquera National Forest (NAFO), located in the municipalities of Faro, Oriximiná and Terra Santa, Forest Management Unit II (FMU-II), 2017 Annual Production Unit (APU / 2017). Control and cost information were conducted through interviews with the responsible technical team, purchase and production control files, and information gathered in the field between August and September 2017. Based on the data, it was observed that the production coefficients accurately estimated the time invested in forest activities, with an average difference of 0.015% in the total cost of forest exploitation when compared to the time reported by the technical team. Logging and the opening of roads and stockyards are the most costly activities of logging and the equipment used, vehicles, tractors and chainsaw, represent more than 75% of the costs of the activities. Finally, the largest cost of wood production in the concession area is the payment of wood to the Brazilian Forest Service (SFB), representing over 63% of the total cost. the area of study of the second chapter was at NAFO Saracá-Taquera, FMU-1A, APU / 2017, Unit of Work 02 (UW-02). By comparing two similar areas, one explored with traditional forest planning (TFP) and the other explored with optimized forest planning (OFP) for the allocation of log yards. It was observed that by taking into account planning alone, the OFP provided a significant reduction in the Euclidean distance tree-yard link, with no large variation in the planned amount of forest roads when compared to the TFP. The average drag distance was reduced by 17.16% and the cost of m³ dragged by 25.76% with OFP